Kidney damage phenylhydrazine and methods of its pathogenetic correction - V M Sirman; B A Nasibullin; L M Shafran; W Zukow; A I Gozhenko (Kazimierz Wielki University, 2017)
In experiments on rats it was found that the administration of phenylhydrazine in doses of 10 mg, 50 mg and 100 mg / kg of body weight accompanied by a dose-dependent morphological damage of the kidneys. By comparing the morphological disorders in kidneys of rats were used for drinking tap water, 1% NaCl solution or a 0.75% NaCl and 0,36% NaHCO3 found that brines possess nephroprotective activity. The greatest protective effect with respect to kidney toxicity with phenylhydrazine possessed solution containing chloride and sodium bicarbonate.